2006
DOI: 10.1002/jbm.a.31017
|View full text |Cite
|
Sign up to set email alerts
|

Combustion synthesis of porous biomaterials

Abstract: This article discusses the unique material manufacturing process of self-propagating high temperature synthesis (SHS) as applied to the making of porous biomaterials. Porous materials have long been considered as the first step toward in-vivo bone tissue engineering and the creation of patient life-time implants. The authors have approached this challenge by utilizing combustion synthesis, to create novel materials such as NiTi + TiC as well as porous forms of materials that are commonly accepted for biomedica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…There appears to be no obvious uniform particle geometry that would indicate sintering of the reactants. Product morphology is indicative of a SHS reaction [2, 7, 52]. …”
Section: 0 Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There appears to be no obvious uniform particle geometry that would indicate sintering of the reactants. Product morphology is indicative of a SHS reaction [2, 7, 52]. …”
Section: 0 Results and Discussionmentioning
confidence: 99%
“…Traditional combustion synthesis methods utilize solid-state reactions of reactant powders [2] whereas decomposition combustion synthesis (DCS) requires the aqueous decomposition and subsequent reconstitution of the reactants into a gelatinous foam prior to ignition [3, 4]. Calcium phosphate DCS is a self-propagating high-temperature synthesis (SHS) process that utilizes the heat generated by the exothermic reaction of urea, calcium nitrate and ammonium phosphate to generate and sustain the propagation of a combustion wave [5–7] through the reactants.…”
Section: 0 Introductionmentioning
confidence: 99%
“…Ayers et al combustion synthesized materials of importance in the biomedical fi eld. They used CaO and P 2 O 5 powders to synthesize calcium triphosphate, Ca 3 (PO 4 ) 2 , in reduced gravity [63] . They concluded that grains displayed a spherical morphology in comparison to the longitudinal -radial shape observed at terrestrial gravity.…”
Section: Microgravity Csmentioning
confidence: 99%
“…This strategy was shown to be highly successful for synthesizing ceramic materials for biological applications [2]. Incorporating blowing agents to synthesis metal alloys has not been widely pursued, yet has recently been shown to be feasible using nanoparticles [3].…”
Section: Introductionmentioning
confidence: 99%